Subacromial Balloon Spacer: Indications, Rationale, and Technique. Issue 2 (20th April 2022) - Dasari, Suhas P.; Khan, Zeeshan A.; Swindell, Hasani W.; Mehta, Nabil; Kerzner, Benjamin; Verma, Nikhil N.
Abstract : Background: Irreparable rotator cuff tears are those that cannot be restored back to their native footprint or those in which any repair will "almost certainly" lead to a structural failure as a result of poor tissue quality, degeneration, or retraction 1 -3 . The InSpace subacromial balloon spacer (Stryker) was developed as a temporary spacer to restore anatomic relationships between the glenoid, humerus, and acromion to improve function and reduce pain associated with this challenging pathology. Description: First, a diagnostic arthroscopy is performed. In addition to evaluating the rotator cuff, care is taken to evaluate the tendinous insertion of the subscapularis as well as the long head of the biceps tendon, the labrum, and the articular cartilage of the joint. Synovectomy, bursectomy, and biceps tenodesis or tenotomy are performed as appropriate. For cases with an intact or repairable subscapularis, an acromioplasty is performed. The balloon size is determined with use of a probe through the lateral portal, measured from 1 cm medial to the superior glenoid rim to the lateral border of the acromion. The balloon-insertion device is advanced through the lateral portal, and the balloon is inflated with sterile saline solution after appropriate subacromial positioning. The balloon is then sealed and detached from the insertional device. Alternatives: Most treatment algorithms attempt to reduce pain and dysfunction with initial nonoperative treatment options 4 . For cases in which nonoperative treatment has failed, several surgical techniques have been described. These include partial rotator cuff repair, graft interposition, graft augmentation, superior capsular reconstruction, tendon transfers, and reverse total shoulder arthroplasty 5 . Rationale: Ideal candidates for this procedure are patients with irreparable symptomatic rotator cuff tears. These patients should primarily complain of pain and have a preserved range of motion. Alternatively, if they have reduced range of motion because of pain, then their range of motion should improve after a corticosteroid injection. It is also important that the patient has an intact or repairable subscapularis. The balloon is beneficial in patients with medical comorbidities that would limit the use of other techniques dependent on biologic tissue healing or that would limit the use of arthroplasty. Poor candidates would be patients with pseudoparalysis, axillary nerve palsy, irreparable subscapularis tears, or severe glenohumeral arthritis (Hamada grade ≥3). Expected Outcomes: A recent randomized clinical trial demonstrated the 2-year efficacy, safety, and benefits of the InSpace subacromial balloon spacer 6 . The authors reported significant early clinical benefit that was maintained over 2 years. Additionally, this benefit was equivalent or superior to the partial-repair control group at all included time points. The multiyear clinical efficacy of the subacromial balloon spacer in that study was similar to that reported by Familiari et al. and Senekovic et al. at 3 and 5 years postoperative, respectively 1, 7 . Together, these studies would suggest that the initial benefit of the subacromial balloon spacer lasts beyond its biodegradation at 12 months postoperatively. Important Tips: Proper placement of the lateral portal should be made parallel to the supraglenoid tubercle. Such placement allows easy insertion and orientation of the balloon at the midpoint of the supraglenoid tubercle. Arthroscopic evaluation of the subscapularis must be performed. For cases with a torn subscapularis, partial or complete repair is recommended to maximize anteroposterior coupling forces that are critical to the function of the balloon. Preservation of the medial bursa and coracoacromial ligament will provide structural constraints against medial migration of the balloon into the supraspinatus fossa. Acromioplasty can be performed to create a smooth articulating surface and minimize friction on the implant, but should only be done in cases in which there is an intact or repairable subscapularis to minimize the risk of anterior escape. Adequate debridement, with acromioplasty as needed, will provide full visualization of the subacromial space to allow proper sizing of the spacer. Proper implant sizing will reduce the risk of subsequent balloon displacement postoperatively. If the measurement of the balloon is between 2 sizes, the larger spacer can be selected to limit displacement. Overinflation of the balloon can cause excessive tension on the deltoid. Underinflation increases the risk of escape. To optimize inflation of the balloon, the senior author prefers to fill the balloon to the recommended maximum volume and then remove saline solution until the balloon reaches the recommended final volume. If there is partial tearing of the long head of the biceps, a tenotomy or tenodesis is recommended. Acronyms and Abbreviations: ROM = range of motion RCT = randomized clinical trial TSA = total shoulder arthroplasty SCR = superior capsular reconstruction RC = rotator cuff ISP = infraspinatus SSP = supraspinatus SSC = subscapularis RI = rotator interval CAL = coracoacromial ligament CA = coracoacromial C = coracoid MRI = magnetic resonance imaging SAD = subacromial decompression PRO = patient-reported outcome FDA = U.S. Food and Drug Administration